Hypertensive Crises in the Adolescent: Evaluation of Suspected Renovascular Hypertension - Indra Wijaya; Parlindungan Siregar (Acta Medica Indonesiana)
Hypertensive crises can be divided into two categories as hypertensive emergency and hypertensive urgency. Most authorities have defined hypertensive emergency as a situation that requires immediate reduction in blood pressure (BP) with parenteral agents because of acute or progressive target organ damage, whereas hypertensive urgency is a situation with markedly elevated BP but without severe symptoms or progressive target organ damage, wherein the BP should be reduced within hours, often with oral agents. Adolescent with hypertension should be suspected of having renovascular hypertension in spite of other causes. This case is presenting a 16-year-old boy with hypertensive crises due to suspected renovascular hypertension. His blood pressure was 240/120 at admission with hypertensive retinopathy grade III and there was increase in creatinine after administering ACE-inhibitor but his renal arteriography revealed normal, other physical examination and laboratory findings was normal. Regarding these findings, the conclusion was this patient got essential hypertension. As many hypertensive crises occur in any ages, clinicians should aware the possibility of renovascular hypertension in young patients with hypertensive crises. An early detection and urgent treatment are needed to prevent the implication of progressive target organ damage.